Intervensi Non Farmakologi dalam Penanganan Konstipasi pada Pasien Stroke - Kristiowati, Suli; Soesanto, Edy; Pohan, Vivi Yosafianti (FORIKES, 2024)
In stroke, disruption of the relationship between the nervous and digestive systems due to blockage of blood vessels in the brain by a thrombus or embolus can result in constipation. Constipation that is not managed effectively will affect the quality of life. Handling of constipation problems in stroke patients can be done with non-pharmacological therapy that does not cause side effects. The purpose of this study was to determine non-pharmacological therapy for treating constipation in stroke patients. This study was a systematic literature review. The source of literature was the database on the app.dimensions.ai website. The literature search was conducted in April 2024, using the keywords